The Italian Footwear Industry: An Empirical Analysis. (13th August 2013) - Pirolo, Luca; Giustiniano, Luca; Nenni, Maria Elena
This paper aims to provide readers with a deep empirical analysis on the Italian footwear industry in order to investigate the evolution of its structure (trends in sales and production, number of firms and employees, main markets, etc.), together with the identification of the main drivers of competitiveness in order to explain the strategies implemented by local actors.